Venlafaxine and desvenlafaxine in the management of menopausal hot flashes - Johnson ED; Carroll DG (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Vasomotor flushes are common complaints of women during and after menopause, affecting about 75 percent of this population. Estrogen therapy is the most effective treatment for hot flashes. However, there are a significant number of women who have contraindications or choose not to use estrogen due to potential risks such as breast cancer and thromboembolic disorders. These women need alternative options. The selective norepinephrine reuptake inhibitors, venlafaxine and desvenlafaxine, have shown efficacy in alleviating hot flashes.Objective: The purpose of this review is to assess the efficacy and tolerability of these two agents for treatment of hot flashes in healthy postmenopausal women.Methods: A literature search of the MEDLINE and Ovid databases from inception to June 2011 was conducted. Randomized controlled trials, published in English, with human participants were included. Studies included postmenopausal women, and trials with breast cancer only populations were excluded.Results: Venlafaxine reduced hot flashes by 37 to 61 percent and desvenlafaxine by 55 to 69 percent. Both agents were well tolerated. The most common adverse effects were headache, dry mouth, nausea, insomnia, somnolence, and dizziness.Conclusion: Based on the evidence, venlafaxine and desvenlafaxine are both viable options for reducing the frequency and severity of hot flashes.